Analysis of Qualitative Studies on ANC Services During the Covid 19 Pandemic at PMB Ana Hasanah - Hasanah Hasanah; Nanik Yuliwati (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background : In this COVID-19 pandemic situation, there are many restrictions on almost all routine services including maternal and newborn health services. Pregnant women are advised to continue to routinely carry out pregnancy checks during the pandemic even though there are service modifications (social distancing). Purpose of Writing: To obtain in-depth information about ANC services during the Covid-19 pandemic at PMB Ana Hasanah. Research Methods: The research used is a qualitative approach with the type of Rapid Assessment Procedures (RAP) research. The informants of this study consisted of 8 pregnant women who made antenatal care visits at PMB Ana Hasanah. While the key informants were husbands or families of pregnant women and Ana Hasanah PMB officers. Research Results: input components, human resources are sufficient and according to standards. Funds are available and sourced from clinic revenue turnover. SOPs are available which refer to the RI Ministry of Health Guidelines. The facilities and infrastructure are complete. For the process component, midwives' independent practice has carried out the flow of antenatal care services and health protocols according to the guidelines, but level 3 PPE is still limited. For the output component, the scope of ANC services has decreased significantly during the pandemic. For the outcome component, pregnant women are satisfied with antenatal care services, but some pregnant women do not have routine checks. Conclusions and Suggestions: The results of this study are expected to provide information to the Mandiri Midwife Practice as a place for maternal and neonatal health services so that they can provide the best service to pregnant women during the pandemic both online and offline so that monitoring of pregnant women during the COVID-19 pandemic can run well.